НАВоий вилояти шаҳар аҳоли ПУНКТларининг ҳудудий таркиби ва демографик кўрсатгичлари - Шерхолов, О.И. (SCIENCE and SOCIETY, 2023)
This article considers the territorial composition of urban settlements in the Navoi region. Demographic indicators were analyzed every five years. Urban settlements were classified by population and grouped by birth and death rates. Settlements established in 2009 were studied by regions. The factors influencing the low number of marriages of convenience in comparison with rural areas, but the high number of divorces, are given. The factors causing a large number of men in the sex composition of the population in the study period are shown. It is determined that the majority of urban settlements and the number of inhabitants correspond to the southern part of the region.
Keywords: city; town; population; birth rate; death rate; migration; marriage; divorce